Prevalence of active trachoma and its associated factors among children aged 1–9 years in previous leprosarium and non-leprosarium areas in eastern Ethiopia: a community-based comparative study - Weldegebreal, Fitsum; Getachew, Mitiku; Mekonnen, Getachew Kabew; Desalew, Assefa; Mekonnen, Shambel; Raru, Temam Beshir; Umer, Ukash; Urgesa, Kedir (Frontiers in Tropical Diseases, 2024)
BackgroundTrachoma is a neglected tropical disease that mainly affects impoverished and marginalized communities with inadequate shelter and sanitation. Nevertheless, the prevalence of active trachoma and the specific factors contributing to it among communities residing in former leprosy settlements in eastern Ethiopia are not well explored. Therefore, the objective of this study was to compare the prevalence of active trachoma and its associated factors among children aged 1-9 years in the previous leprosarium and non-leprosarium areas, as well as urban and rural areas in eastern Ethiopia.MethodsA community-based comparative cross-sectional study was conducted among 580 systematically selected households from January 1 to 30, 2024. Data were collected by interviewing the children’s caregivers, observing the child and environment, and conducting a clinical examination of their eyes. Data were entered in EpiData version 4.6 and exported to Statistical Package of Social Science (SPSS) version 26 software for analysis. A chi-square test was also done. The association was presented as an adjusted odds ratio with a 95% confidence interval, and variables with a p-value less than 0.05 were regarded as statistically significant.ResultsThe overall prevalence of active trachoma was 12.9% (95% CI: 10.5%-15.3%). The prevalence of active trachoma was 15.6%, 9.8%, 18.3%, and 7.5% among children in previous leprosy and non-leprosy settlements and rural and urban areas, respectively (x²=5.65, p-value = 0.017). Having eye discharge (AOR = 10.7’; 95% CI: 4.32, 26.51), latrine distance from home of less than 10 m(AOR=3.12; 95% CI: 1.16–8.34), being a rural resident (AOR=4.1; 95% CI: 1.69-10.18), presence of solid waste around their home (AOR=6.5; 95% CI: 2.14-19.72), and household monthly income less than 5000 Ethiopian birrs (AOR=2.9; 95%CI: 1.04-8.30) were statistically associated with active trachoma in the previous leprosy settlements. In the non-leprosy settlements, children who had eye discharge (AOR = 7.6; 95% CI: 5.37, 58.05), latrine distance from home of less than 10 m (AOR=3.12; 95%CI: 1.11, 8.77), habit of playing with soil (AOR=9.0; 95% CI: 2.92, 28.24), and presence of animal dung (AOR=6.98; 95% CI: 3.44, 48.47) were statistically associated with active trachoma.ConclusionIn this study, the prevalence of active trachoma among children aged from 1-9 years old was higher than the WHO target for the elimination of active trachoma (<5%) in every district. Therefore, targeted treatments and raising awareness on proper hygiene and sanitation are required to alleviate the problem.